2010
DOI: 10.1017/s1460396910000348
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on accessibility of palliative radiation therapy in the management of prostate cancer in British Columbia

Abstract: Timely administration of palliative radiation therapy (PRT) to manage symptoms derived from advanced prostate cancer is necessary to help alleviate discomfort and improve quality of life. Despite PRT being an effective treatment, analyzing utilization rates in British Columbia (BC), Canada for palliative purposes implies it is an under-utilized medical resource. Access to and utilization of radiation therapy (RT) is lower in remote geographical regions and higher in urban regions where a cancer care facility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Another was that North East and East Kootenay HSDAs are close to the neighbouring province of Alberta. It is possible that some decedents were referred to the radiotherapy centres in Alberta, which would not be captured in our data [15]. These findings were consistent with other studies that showed the detrimental effect of increased travel time on reduced PRT use existed previously, affecting patients as early as 1986 [15, 16].…”
Section: Discussionsupporting
confidence: 80%
“…Another was that North East and East Kootenay HSDAs are close to the neighbouring province of Alberta. It is possible that some decedents were referred to the radiotherapy centres in Alberta, which would not be captured in our data [15]. These findings were consistent with other studies that showed the detrimental effect of increased travel time on reduced PRT use existed previously, affecting patients as early as 1986 [15, 16].…”
Section: Discussionsupporting
confidence: 80%
“…Individuals living in the Circumpolar North may have to travel extensive distances to reach other cities or even other countries for the health services they need, especially if these are specialised services [11,[14][15][16]20,22,28,31,32]. For example, researchers found that some patients living in Greenland must endure 6 to 7 h of travel time to gain access to advanced care in Denmark [15].…”
Section: Distance To Urban Centresmentioning
confidence: 99%
“…Cancer diagnoses were categorised according to the International Classification of Disease (ICD) codes ( n = 19), SEER [ 17 , 18 ] ( n = 2) and the Cancer Agency Information System (CAIS) [ 30 ] ( n = 1). Cancer diagnoses were identified using administrative health database claims ( n = 11), cancer registries ( n = 10), death certificates [ 31 ] ( n = 1), health insurance claims [ 32 ] ( n = 1), palliative program enrolment records [ 33 ] ( n = 1) and linked cancer registry and death certificate data [ 34 ] ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…As measures of specialist palliative care two studies examined SPC usage [ 31 , 37 ], 10 studies examined the use of hospice care [ 12 , 14 , 15 , 16 , 17 , 18 , 32 , 38 , 39 , 40 ], two studies assessed receipt of PRT [ 30 , 34 ] and one study assessed receipt of pharmacotherapy [ 13 ] ( Table 1 ). Regarding SPC usage, Burge et al [ 37 ] found residents in rural regions compared with urban were less likely to be registered with a palliative care program (PCP) after controlling for age (0.8 (0.7–1.0)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation